(untitled) (Research Announcements "Heritage BG", 2025)
The article is devoted to the emergence and development of the modern forestry profession in the Balkans until the First World War. The main focus is on the establishment of professional associations of foresters in the region. The development of forestry services and the education of foresters in the Balkan countries is also discussed. References: Kostov, Alexandre. (2016). Gorskoto delo v Balgariya (1879-1914): institutsionalno izgrazhdane i nabirane na kadri. In: Istorikat – izsledovatel i populyarizator. Sbornik v chest na 70-godishninata na akademik Georgi Markov. Sofia, 102-116. Kostov, Alexandre. (2016). Nachaloto na modernoto gorsko delo na Balkanite: gorski sluzhbi I lesovadno obrazovanie. – Spisanie na BAN, No. 2, 30-38. Đirković, Miloš. (1926). Šumarstvo i šumarske prilike u Srbiji. In: Pola stoljeća šumarstva 1876-1926. Spomenica Jugoslovenskog šumarskog udruženja o slavi njegove pedesetogodišnjice (ed. Aleksandar Ugrenović). Zagreb, 153-164. Dojković, Viljem. (1926). Hrvatsko šumarsko društvo (1871-1921). In: Pola stoljeća šumarstva 1876-1926. Spomenica Jugoslovenskog šumarskog udruženja o slavi njegove pedesetogodišnjice (eds. Aleksandar Ugrenović). Zagreb, 23-36. Dursun, Selçuk. (2007). Forest and the State: History of forestry and forest administration in the Ottoman Empire. Ph.D Dissertation, Institute of Social Sciences, Sabanci University. Istanbul. Giurescu, Constantin. (1980). A History of Romanian Forest. Bucharest. Grίspos, Pάnos. (1973). Δασική ιστορία της νεωτέρας Ελλάδος, Athens. Ivănescu, Dimitru. (1972). Din istoria silviculturii româneşti. Bucharest. Kostov, Alexandre. (2018). Professional Associations of Balkan Engineers until the First World War. – Papers of BAS Humanities and Social Sciences, No. 5(2), 155-169. Özdönmez, Metin, Abdi Ekizoðlu. (1993). Tanzimat ve Meşrutiyet Dönemleri ormancýlýðýnda katkýlarý olan yabancý uzmanlar. – Journal of the Faculty of Forestry Istanbul University, No. 43(3-4), 57-68. Panagouli, Eleni. (2016). La rencontre de la ville et de la forêt. L’action publique et les territoires de la nature en Grèce. PhD Dissertation, L’École des hautes études en sciences sociales. Paris.